2019
DOI: 10.1117/1.jrs.13.044519
|View full text |Cite
|
Sign up to set email alerts
|

Development of aboveground mangrove forests’ biomass dataset for Southeast Asia based on ALOS-PALSAR 25-m mosaic

Abstract: Development of aboveground mangrove forests' biomass dataset for Southeast Asia based on ALOS-PALSAR 25m mosaic,"Abstract. Southeast Asia (SEA) has the largest mangrove forest area in the world, which plays an important role in the global carbon cycle and is helping to mitigate climate change. In order to manage the mangrove forests in SEA, their total biomass needs to be determined. However, development of a biomass dataset based on field survey is time consuming. An aboveground biomass (AGB) dataset of mangr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
5
2
Order By: Relevance
“…However, the AGB of PMF was relatively low (91.49 t ha -1 ) compared to the other natural mangrove forests in Thailand and other tropical sites (Table 3). Darmawan et al (2019) reported that AGB of primary mangrove forest in Chumphon Province, Thailand, dominated by R. apiculata, was 231.40 t ha -1 , which was significantly higher than that of PMF in our study. In addition, the AGB of PMF was lower than that of primary mangrove forests in the tropics such as in Indonesia (252.56 t ha -1 ) (Darmawan et al 2019), Sulaman Lake Forest Reserve, Malaysia (134.59 t ha -1 ) (Suhaili et al 2020) and the Sundarbans mangrove forest, Bangladesh (153.70 t ha -1 ) (Kamruzzaman et al 2018).…”
Section: Vegetation Biomasscontrasting
confidence: 54%
See 1 more Smart Citation
“…However, the AGB of PMF was relatively low (91.49 t ha -1 ) compared to the other natural mangrove forests in Thailand and other tropical sites (Table 3). Darmawan et al (2019) reported that AGB of primary mangrove forest in Chumphon Province, Thailand, dominated by R. apiculata, was 231.40 t ha -1 , which was significantly higher than that of PMF in our study. In addition, the AGB of PMF was lower than that of primary mangrove forests in the tropics such as in Indonesia (252.56 t ha -1 ) (Darmawan et al 2019), Sulaman Lake Forest Reserve, Malaysia (134.59 t ha -1 ) (Suhaili et al 2020) and the Sundarbans mangrove forest, Bangladesh (153.70 t ha -1 ) (Kamruzzaman et al 2018).…”
Section: Vegetation Biomasscontrasting
confidence: 54%
“…Darmawan et al (2019) reported that AGB of primary mangrove forest in Chumphon Province, Thailand, dominated by R. apiculata, was 231.40 t ha -1 , which was significantly higher than that of PMF in our study. In addition, the AGB of PMF was lower than that of primary mangrove forests in the tropics such as in Indonesia (252.56 t ha -1 ) (Darmawan et al 2019), Sulaman Lake Forest Reserve, Malaysia (134.59 t ha -1 ) (Suhaili et al 2020) and the Sundarbans mangrove forest, Bangladesh (153.70 t ha -1 ) (Kamruzzaman et al 2018). The belowground biomass (BGB) of MF3 and MF14 increased drastically from 12.58 t ha -1 to 74.76 t ha -1 after rehabilitation.…”
Section: Vegetation Biomasscontrasting
confidence: 54%
“…Over the past 10 years, various attempts have been made to obtain mangrove AGB estimations using simple linear regression [79] and multi-linear regression [18,19,80]; these attempts resulted in low performance with R 2 values ranging from 0.43 to 0.65. In recent years, ML algorithms such as Gaussian process regression, multi-layer perception neural networks, SVR, and RFR techniques have been employed to retrieve mangrove AGB, as reported in a number of published case studies [8,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used method is to extract pixel values of Visible-Infra Red (V-IR) bands (EM wave lenght 600 nm-950 nm) from medium resolution satellite images such as Landsat ETM 7, Landsat 8 OLI, ALOS, or the most recent Sentinel 2A/2B [7][8][9]. However, detection via the above mentioned passive satellites remote sensing is frequently limited by weather and thus cannot penetrate cloud cover.…”
Section: Introductionmentioning
confidence: 99%